PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA MATHLA’UL ANWAR PONTIANAK - Ramadhan, Ramadhan; Sulistyarini, Sulistyarini; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect implementation the problem based learning model on geography learning in class XI IPS 2 Mathla'ul Anwar Pontianak. The research menthod used is quasi experimental with quantitative research forms. The source of the research data with a sampe of 27 student in the experimental class 28 student in the control class. Data collection techiques consirt of direct data collectionvand measurement techniques while the data collection tools used was multiple choise written test 20 questions. According to the statistical calculation, the average result of the control group as 88,53 and 91,7037for the experimental group. The learning result of hypothesis testing using t-test obtained as 4,2052 and (α =5% which dk -2 = 27+28-2 = 53) was (2,00735). Then, is accepted. According to calculation of the effect size showed 0,3720 in the medium category. Based on these emplemention, it can be concluded that there was an effect of the implementation the problem based learning model on geography learning in class XI IPS 2 Mathla’ul Anwar Pontianak.Keyword: Problem Based Learning model and Learning Outcomes